2013
DOI: 10.1155/2013/543174
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Improves Bladder and Bowel Function in Patients with Traumatic Spinal Cord Injury: Results from a Prospective Observational Study

Abstract: In order to explore the effect of electroacupuncture (EA) for chronic bowel and bladder dysfunction after traumatic spinal cord injury, 14 patients were treated with electroacupuncture once a day, five times a week for the first four weeks, and once every other day, three times a week for the following four weeks. The patients were then followed up for six months. After treatment, four (4/14, 28.57%) patients resumed normal voiding; six (6/14, 42.86%) resumed normal voiding for no less than half of all micturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
(35 reference statements)
1
8
0
4
Order By: Relevance
“…This will assist in the implementation of preventive measures and reasonable allocation of medical resources. [12][13][14] Despite some research that has been conducted on the prevalence of TSCI in China (Table 1), there have not been any regional estimates of the incidence or epidemiological characteristics of TSCI in Heilongjiang province, northeast China. Social and economic circumstances of Heilongjiang province are different relative to other areas of China.…”
Section: Discussionmentioning
confidence: 99%
“…This will assist in the implementation of preventive measures and reasonable allocation of medical resources. [12][13][14] Despite some research that has been conducted on the prevalence of TSCI in China (Table 1), there have not been any regional estimates of the incidence or epidemiological characteristics of TSCI in Heilongjiang province, northeast China. Social and economic circumstances of Heilongjiang province are different relative to other areas of China.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Voiding disorder is another characteristic of bladder dysfunction caused by TM. Our previous observational studies on patients with cauda equina injury 34 and with traumatic spinal cord injury 18 indicated that EA could reduce the postvoid RUV by 303.6±148.8 mL and 190.29±101.87 mL, respectively. The present study also demonstrated a 100 (53–393) mL decrease in RUV after EA treatment.…”
Section: Discussionmentioning
confidence: 95%
“…We have difficulty in drawing a definitive conclusion that EA is more effective than other treatments. EA has been widely used in China; it relieves pain for many patients safely and effectively [ 63 , 64 ], and its mechanism and effect are worthy of our in-depth study.…”
Section: Discussionmentioning
confidence: 99%